2021
DOI: 10.3389/fpls.2021.737219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Switchgrass TDIF-like Genes on Arabidopsis Vascular Development

Abstract: As a member of the CLAVATA3 (CLV3)/EMBRYO SURROUNDING REGION (CLE) family, the dodecapeptide tracheary element differentiation inhibitory factor (TDIF) has a major impact on vascular development in plants. However, the influence of polymorphisms in the TDIF peptide motif on activity remains poorly understood. The model plant, Arabidopsis provides a fast and effective tool for assaying the activity of TDIF homologs. Five TDIF homologs from a group of 93 CLE genes in switchgrass (Panicum virgatum), a perennial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The phenomenon of a single gene encoding for multiple peptide domains has been reported in a number of plant species ( Delay et al., 2013 ; Hou et al., 2014 ; Goad et al., 2017 ; Tian et al., 2021 ). In this study, a number of TaSSP genes were identified to encode multiple peptide domains, including CLE, HEVEIN and HAIRPININ domains ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of a single gene encoding for multiple peptide domains has been reported in a number of plant species ( Delay et al., 2013 ; Hou et al., 2014 ; Goad et al., 2017 ; Tian et al., 2021 ). In this study, a number of TaSSP genes were identified to encode multiple peptide domains, including CLE, HEVEIN and HAIRPININ domains ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The BLAST method is often used to predict members of the known SSP families. For example, the poplar CLEL family and the switchgrass CLE family were identified via BLAST ( Tian et al., 2019 ; Tian et al., 2021 ). Another common approach for SSPs prediction is HMMER ( Eddy, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation